2009
DOI: 10.1007/s10900-009-9163-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of State Firearm Mortality and Mental Health Care Resources

Abstract: A disproportionate share of firearm suicides and homicides are committed by individuals who have a psychiatric diagnosis, many with a history of substance abuse. This study assessed whether selected variables that potentially indicate increased access to mental health care or known demographic risk factors for firearm trauma best predicted state variations in firearm homicide and suicide. Partial correlation coefficients indicated that the proportion of the population within a given state that was African Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…A similar pattern was seen with mental health providers, although no statistically significant associations were found. These findings are analogous with previous research which has demonstrated a relationship between indices of access to healthcare and suicide, including density of physicians and psychiatrists (Tondo et al , 2006; Arria et al , 2011), and also between allocation of state-level mental health resources and firearm suicide (Price et al , 2009). And, while the number of preventable hospital stays is a quality of care indicator in the CHR data, it may also likely reflect poorer access to primary care (Bindman et al , 1995; Backus et al , 2002; van Loenen et al , 2014).…”
Section: Discussionsupporting
confidence: 90%
“…A similar pattern was seen with mental health providers, although no statistically significant associations were found. These findings are analogous with previous research which has demonstrated a relationship between indices of access to healthcare and suicide, including density of physicians and psychiatrists (Tondo et al , 2006; Arria et al , 2011), and also between allocation of state-level mental health resources and firearm suicide (Price et al , 2009). And, while the number of preventable hospital stays is a quality of care indicator in the CHR data, it may also likely reflect poorer access to primary care (Bindman et al , 1995; Backus et al , 2002; van Loenen et al , 2014).…”
Section: Discussionsupporting
confidence: 90%
“…37 Firearm ownership is greater in rural areas, and greater state-level firearm ownership has been associated with greater firearm suicide mortality. 27 Among suicide methods, firearms sadly have the highest case-fatality rates. 26 As Miller and Hemenway noted, "A suicide attempt with a firearm rarely affords a second chance."…”
Section: Discussionmentioning
confidence: 99%
“…Both police and ambulance systems play important roles in responding to suicide crises in the community [38]. Education and welfare expenditure also contributes to the prevention of suicide [26,39]. Furthermore, the increasing expenditure of public works on infrastructure is traditionally considered to contribute to the improvement of economic and mental wellbeing via the generation of employment opportunities [37].…”
Section: Effects Of Regional Governmental Expenditure On Suicide Mortality Disaggregated By Gendermentioning
confidence: 99%